America. - J. & G. Menzies ([J. Thomson & Co.], 1819)
Map shows major cities, political divisions, physical features, and areas of Native American habitation; Mississippi River as boundary between [French] Louisiana and the United States; Greenland, islands in the Pacific and Atlantic Oceans, western Europe, west coast of Africa, and the Mediterranean Sea. Includes dates of exploration on northern coast of Alaska. Relief shown pictorially. Scale not given.